Natural fiber thermoplastic composites in terms of new production technologies: A review - Akdogan, Anil; Vanli, Ali Serdar (PAMUKKALE UNIV, 2020)
This paper investigates Natural Fiber Thermoplastic Composites (NFTC) which take attention of the researchers and the market having aesthetic and low maintenance properties in many applications. Additive usage is an increasing application for NFTC production to get into the novel markets satisfying strong performance requirements and life stability interests of users. In this article, polymer blends from natural resources including bio-based additives for polymer composites were introduced. Afterwards, favorite additive types and most effective pelletizing processes in literature were analyzed to improve composite productivity. At the end of the paper, the common NFTC production technologies are discussed. A specially designed compounding extruder which is designed to overcome production difficulties and supply high processing performances is introduced. At the end of conducted experiment, the obtained production output rate is presented.
Keywords: Polymer composites; Natural fiber thermoplastic composites; Manufacturing technologies; Productivity; MECHANICAL-PROPERTIES; REACTIVE EXTRUSION; POLYMER BLENDS; PP COMPOSITES; WOOD FIBER; COMPATIBILIZATION; STARCH; HYDROLYSIS; AGENT; CHIPS; Engineering